Association between the atherogenic index of plasma and incident hypertension across different blood pressure states: a national cohort study - Degang Mo; Peng Zhang; Miao Zhang; Hongyan Dai; Guoan Wang (Cardiovascular Diabetology)
Abstract Background Hypertension is a major public health concern, making effective preventive strategies essential. The atherogenic index of plasma (AIP), a new lipid metabolic index that is associated with insulin resistance and cardiovascular diseases. However, the association between AIP and the incidence of hypertension remains unexplored. To address this knowledge gap, we designed a large-scale retrospective cohort study to investigate the association between AIP and the occurrence of hypertension across different blood pressure (BP) states, including individuals with normal BP and those with elevated BP. Methods This retrospective cohort study used data from the China Health and Retirement Longitudinal Study (CHARLS) involving participants aged 45 and older, assessed in 2011 and followed up in 2020. AIP was calculated using the logarithmic ratio of triglycerides (TG) to high-density lipoprotein cholesterol (HDL-C). Logistic regression models, restricted cubic splines models, and threshold analyses were employed to examine the relationship between AIP and the incidence of hypertension. Receiver Operating Characteristic analysis was utilized to assess the ability of AIP to predict the incidence of hypertension. Subgroup analyses were conducted across various demographic and health-related factors. Sensitivity analyses were employed to address biases arising from self-reported data. Results Among 6540 participants, 1909 (29.19%) developed hypertension over nine years. The AIP is an independent risk factor for the development of hypertension, with an adjusted odds ratio of 1.84 [95% confidence interval (CI) 1.41–2.39, p < 0.001] in individuals with normal BP and 1.88 (95% CI 1.40–2.52, p < 0.001) in those with elevated BP. A nonlinear relationship between AIP and the incidence of hypertension was identified in both normal BP and elevated BP population. AIP has a better predictive ability for the occurrence of hypertension compared to the single indicators of TG and HDL-C. Age significantly impacted AIP’s predictive value, especially in those aged 45 to 60 in normal BP population. Sensitivity analyses further validated the nonlinear relationship between AIP and the occurrence of hypertension. Conclusions AIP is a significant predictor of hypertension, demonstrating a nonlinear association with its occurrence in normal BP and elevated BP population. Trial registration Not applicable. Graphical abstract